Evaluation of novel dual-hit models of 'schizophrenia-like' symptoms in the rat - Gaskin, Philip Laurence Roy (2014)
Schizophrenia is a debilitating disorder comprising positive, negative and cognitive deficits with a poorly-defined neurobiological basis. Animal models with greater translational reliability and validity are essential to develop improved therapies and aid understanding of disease aetiology. This thesis utilised the well-established isolation rearing developmental disruption model of schizophrenia in the rat as the base for producing novel ‘dual-hit’ combination models of the disease, with the aim of improving disease validity and model robustness. Pharmacological insults were added to the isolation rearing model, first in the form of prenatal administration of the antimitotic agent methylazoxymethanol (MAM), and subsequently perinatal treatment with the N-methyl-D-aspartate receptor antagonist phencyclidine (PCP). The resulting ‘dual-hit’ models were assessed for behavioural and neurobiological validity to schizophrenia, and the incurred deficits challenged with the atypical antipsychotic risperidone and the putative adjunct therapy lamotrigine.